(3ebOeI aj EOGQI GdEfJGL hGdYedjGJ (B/s - (3HOjhj, eMeO GdMSjfs ((3YeGf(B: s (3OGQ GdefGgL(B, s, 2004)
(3ebOeI aj GOGQI GdGfJGL,fXGe eYdheGJ GdGfJGL,GNJHGQ ehbY GdeTQhY,GdJQJjH GdOGNdj ddeTQhY,OQGSI GdMQcI hGdhbJ,GOGQI GdGfJGLjI,GdWGbI GdGfJGLjI,GOGQI GdLhOI GdTGedI(B.s
(3GdeQGLY U(B. 195s
Keywords: (3EOGQI GdEfJGLs; (3GdLhOI GdTGedIs